(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2023)
Abstract: The research seeks to explain the role of the international auditing standard (3402) in the auditor’s procedures, where the importance of the research stems from the adoption of international auditing standards in the Iraqi environment, including the standard (3402) of assurance engagements that the external auditor performs by submitting reports on the design of control tools and their operational effectiveness in a service facility that provides the beneficiaries with a service. To provide useful information for service organizations The control tools are of great benefit in rationalizing decisions, and many recommendations have been reached, the most important of which is that the application of the international auditing standard (3402) by the service organization leads to strengthening audit procedures, that relying on the reasonable assurance process for the purpose of reducing risks to an acceptable level and enhancing confidence among the beneficiaries.